Players’ continuous willingness to play in MOBA game ranking mode: through the lens of self-determination theory and social comparison theory - Tiansheng Xia; Xiaowu Lin; Xiaohong Mo; Qiaomei Su; Shiyao Ding (Humanities & Social Sciences Communications, 2024)
Abstract Multiplayer Online Battle Arena (MOBA) games are a popular genre in the current gaming field, and the highly competitive ranking mode is one of the core parts of the gameplay, and the study of the factors affecting players’ continuous willingness to play is a necessary issue to ensure the sustainable profitability of these games. This study has developed a conceptual model delineating the continuous willingness of players within the MOBA game ranking mode, employing the frameworks of self-determination theory (SDT) and social comparison theory (SCT). In this study, 396 valid data samples were collected using questionnaire method. The results show that, social comparison enhances players’ continuous willingness and avatar identification, and indirectly enhances their continuous willingness through mediation by avatar identification, while game frustration has a significant positive moderating effect in both paths. This study contributes to both theoretical explorations and practical approaches to MOBA game ranking mode.